ESP Implementation and English Proficiency of the Indonesian Nurses to Face Global Health Challenges - Suhria, Suhria; Irmayanti, Irmayanti; Arham, Muhammad (Pascasarjana Universitas Negeri Makassar, 2025)
This study uses a quantitative descriptive method with a sequential sampling technique to examine the application of English for Specific Purposes (ESP) among nurses in addressing global health challenges in the 21st century. The sample consisted of 12 nurses working in various settings, such as hospitals, clinics, and health centres, in Sulawesi and Kalimantan islands. Through a questionnaire comprising 10 closed-ended questions and 3 open-ended questions, the study evaluated the use of ESP in the workplace and the English language skills of the participants. The results, presented in a percentage table, indicate that the adoption of ESP in the workplace remains low, despite nurses having a strong understanding of advanced medical technology. However, there is a positive attitude toward international engagement, including participation in international seminars, preparation of professional correspondence in English, and volunteer activities in English-speaking countries. These findings underscore the need for targeted institutional training and support programs to enhance nurses' English language competencies and global skills, enabling them to contribute effectively to international health services. The study has limitations, including a small sample size that restricts the generalizability of the findings across Indonesia. Nevertheless, the inclusion of participants from diverse workplaces offers valuable insights into the use of English in central and eastern Indonesia. Future research should explore larger and more diverse samples and investigate the long-term impact of ESP training on professional development and global readiness among nurses.